2008
DOI: 10.1039/b717773a
|View full text |Cite
|
Sign up to set email alerts
|

A novel mediator–polymer-modified anode for microbial fuel cells

Abstract: A high-performance anode system based on a combination of mediator-polymer-modified graphite felt and bacteria capable of reducing extracellular materials shows significant potential for practical use in microbial fuel cells (MFCs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 15 publications
1
44
0
Order By: Relevance
“…Previous research showed that anode modifications using nanomaterials could increase the electrochemical activity of outer-membrane c-type cytochromes, leading to the enhanced DET in S. oneidensis MR-1 (Deng et al, 2010;Peng et al, 2010;Huang et al, 2011). Meanwhile, several efforts were also made on the physical and chemical immobilization of electron shuttles directly onto electrode to improve the shuttle-mediated EET efficiency (Adachi et al, 2008;Feng et al, 2010;Wang et al, 2011). Here, our work implied that it was possible for improved physical absorption of electron shuttles on electrode interfaces by nitrogen doped modification on electrode materials, providing a new approach in the rational design of novel electrode materials for high-performance MFCs and other bioelectrochemical systems.…”
Section: Referencesmentioning
confidence: 99%
“…Previous research showed that anode modifications using nanomaterials could increase the electrochemical activity of outer-membrane c-type cytochromes, leading to the enhanced DET in S. oneidensis MR-1 (Deng et al, 2010;Peng et al, 2010;Huang et al, 2011). Meanwhile, several efforts were also made on the physical and chemical immobilization of electron shuttles directly onto electrode to improve the shuttle-mediated EET efficiency (Adachi et al, 2008;Feng et al, 2010;Wang et al, 2011). Here, our work implied that it was possible for improved physical absorption of electron shuttles on electrode interfaces by nitrogen doped modification on electrode materials, providing a new approach in the rational design of novel electrode materials for high-performance MFCs and other bioelectrochemical systems.…”
Section: Referencesmentioning
confidence: 99%
“…Recently polymeric quinone was used to electrically connect photosystem II to the electrode, which functioned as the anode of a water splitting photo-bioelectrochemical cell (Figure 15(a)). 84 Quinonemodified electrodes were also used for efficient electron exchange with bacterial cells and applied to sensing toxic substances metabolized by bacteria 85 as well as increasing power output of microbial fuel cells [86][87][88] (Figure 15(b)). Quinone-functionalized chitosan electrodes could be used as a biological redox capacitor that can exchange electrons with biological components in solution, and later convert the amount of charge stored into electronic signal (Figure 15(c)).…”
mentioning
confidence: 99%
“…Anode modification has been reported to be an effective alternative to chemical binding of mediators. It has been investigated and suggested by several authors based on economical effectiveness and expected successful application at large scale . Based on reviewed literature, ammonia and heat treatment are the most economical and practical for large‐scale implementation.…”
Section: Anode and Cathode Modificationmentioning
confidence: 99%